Composition and Physico-Chemical Properties of Meat from Capons Fed Cereals - Olga Díaz; Luisana Rodríguez; Alexandr Torres; Ángel Cobos (Journal of Integrative Agriculture, 2013)
Chemical composition, physico-chemical properties and fatty acid composition of breast and drumstick meat from capons (castrated male cockerels) fed cereals were studied. Three groups of capons were reared. One group was fed ad libitum the same commercial diet until the 4th mon of life. The last month of its life, the capons of this group were fed corn. The second and third group of capons were fed the same diet from caponization. The second group was fed mixture of corn (50%) and wheat (50%). The third group of capons was fed 2/3 corn and 1/3 mixture of corn (50%) and barley (50%). Capons were reared under free-range conditions and slaughtered at 150 d of age. Caponization was performed at 48 d. No significant effects of feeding in chemical composition, pH, water holding capacity, drip and cooking losses and texture of the meat were observed. The meat of the third group (capons fed 83% corn) was more yellow and showed higher content of C18:2 than that of the other capons.